Korea, its history, its people, and its commerce - Hamilton, Angus (J. B. Millet Co., 1902)
This book introduce about outline of history, land and folk, a city of peace, costume, manners, and morals, education and crime. Korean industries, Korean scenery, mining and hunting, travelling in Korea...